2014
DOI: 10.1116/1.4862543
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial properties and cytocompatibility of tantalum oxide coatings with different silver content

Abstract: Tantalum (Ta) oxides and their coatings have been proved to increase their applications in the biomedical fields by improving osseointegration and wear resistance. In this study, Ta oxide coatings containing different proportions of Ag are deposited on SS304 materials. A twin-gun magnetron sputtering system is used to deposit the tantalum oxide-Ag coating. In this study, Staphylococcus aureus, which exhibits physiological commensalism on the human skin, nares, and mucosal and oral areas, is chosen as the model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Furthermore, AgNPs incorporated on the implant surface by sputtering can increase water contact angle and improve hydrophobicity of the substrate surface. 113 It was found that with a decreased sputtering time, surface roughness and wettability were higher. An increasing roughness value is well known to be associated with increased osteoblast adhesion.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Furthermore, AgNPs incorporated on the implant surface by sputtering can increase water contact angle and improve hydrophobicity of the substrate surface. 113 It was found that with a decreased sputtering time, surface roughness and wettability were higher. An increasing roughness value is well known to be associated with increased osteoblast adhesion.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Figure 4b shows the elemental diffusion of Ta, Zr and O in the diffusion zone, respectively. Here, the non-steady diffusion was caused by bombardment of argon ions during the fabrication process of Ta coating, so Fick's second law was employed to evaluate the non-equilibrium diffusion between the Ta coating and the substrate [17,24]: (1) where D, t and x are the diffusion coefficient, time and location, respectively. The concentration of any diffusing location, C, could be got as:…”
Section: Discussionmentioning
confidence: 99%
“…In the high-resolution spectrum of Ta 4f (Figure 8b), two peaks located at the binding energy position of 25.8 eV and 27.7 eV correspond to the characteristic peaks of Ta 4f 7/2 and Ta 4f 5/2 , respectively, indicating that the chemical state of Ta on the surface of C3 sample is Ta 2 O 5 [17]. energy position of 531.3 eV, 530.2 eV and 529.8 eV could be attributed to Ta2O5, CuO and Cu2O, respectively [54][55][56]. These results show that the chemical state of the Ta element in Cu-MTa2O5 composite coating is Ta2O5, while both CuO and Cu2O existed as state Cu elements.…”
Section: Microstructure Characterizationmentioning
confidence: 94%
“…In high-resolution XPS spectrum of O 1s (Figure 8f), three deconvolution peaks at binding energy position of 531.3 eV, 530.2 eV and 529.8 eV could be attributed to Ta 2 O 5 , CuO and Cu 2 O, respectively [54][55][56]. These results show that the chemical state of the Ta element in Cu-MTa 2 O 5 composite coating is Ta 2 O 5 , while both CuO and Cu 2 O existed as state Cu elements.…”
Section: Microstructure Characterizationmentioning
confidence: 99%